2014
DOI: 10.1155/2014/651060
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of the Sources of Construction Waste

Abstract: The construction industry is traditionally environmentally unfriendly. The environmental impacts of construction waste include soil contamination, water contamination, and deterioration of landscape. Also, construction waste has a negative economic impact by contributing additional cost to construction due to the need to replace wasted materials. However, in order to mitigate waste, construction managers have to explore management options, which include reduction, recycling, and disposal of wastes. Reduction h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…It was concluded that efficient materials procurement measures could help in minimising CDW and financial loss of projects. According to a study carried out in the UK by Fadiya et al (2014), it is claimed that inefficient materials procurement, among other eight factors, contributes about 11.2% towards total generated CDW as shown in Figure 6. Also, Ajayi et al (2017a) claimed that materials procurement is responsible for purchasing the wasted materials, and it was also claimed that materials procurement contributes up to 50% of the total project cost.…”
Section: Construction Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that efficient materials procurement measures could help in minimising CDW and financial loss of projects. According to a study carried out in the UK by Fadiya et al (2014), it is claimed that inefficient materials procurement, among other eight factors, contributes about 11.2% towards total generated CDW as shown in Figure 6. Also, Ajayi et al (2017a) claimed that materials procurement is responsible for purchasing the wasted materials, and it was also claimed that materials procurement contributes up to 50% of the total project cost.…”
Section: Construction Industrymentioning
confidence: 99%
“…Different factors contributing to construction and demolition waste (CDW) generation in the UK.Source:Fadiya et al, 2014. …”
mentioning
confidence: 99%
“…Construction methods and planning (COPL) and material and procurement (MAPR) are surprisingly the categories of low impact. Adewuyi and Otali [47] and Fadiys et al [49] also confirmed that design and documentation was the leading source of construction waste. On the basis of the research of Ekanayake and Ofori [39], design, operational, procurement, and material handling contribute to increase waste on the construction site.…”
Section: Discussionmentioning
confidence: 90%
“…A study by Fadiya et al [49] found nine sources of construction waste in the U.K. construction industry. These were residual, design, handling, data error, operations, others, misplacement, weather, and vandalism.…”
Section: Construction Materials Waste Generation Factorsmentioning
confidence: 99%
“…Effective implementation of construction waste sorting requires a wide range of factors involving human beings, management, technology, environment and resources [57]. Furthermore, a reliable estimation of costs associated with waste flows will help decision-makers to enhance the appropriate strategy that can mitigate the C&DW generation [58].…”
Section: Regional Approach Of Sustainable Candd Waste Management Systemmentioning
confidence: 99%